AQUATIC TOXICITY BIOASSAY OF CASSAVA MILL EFFLUENT USING TADPOLES (SCLEROPHRYS REGULARIS) (FUDMA JOURNAL OF SCIENCES, 2025)
During the production of garri, starch and tapioca from cassava, cassava effluents are usually produced as by-product and this by-product contains cyanide and other substances. This study was intended to investigate a 96-hour toxicity test of cassava effluent on tadpoles to check the aquatic environmental health status. Two hundred and ten (210) tadpoles with length and weight ranging from 2.8 -3.5 cm and 0.24 -0.47 mg respectively were collected from a puddle, 150 - 200m from the cassava mill shed and were randomly divided in tens and in duplicate into group A,B,C,D,E and F. Group A is the control. Group B, C, D, E and F were treated with 5ml/L, 10ml/L, 15ml/L, 20ml/L and 25ml/L of the cassava mill effluent with an LC50 of 7.6ml/L. Result showed that there was no death in 5ml/L group B in the 96 hours toxicity test compared with the control. However, in the 10ml/L group C there was a total death of 8 tadpoles in 24, 48, 72 and 96hours of exposure compared with the control. In 15ml/L, 20ml/L and 25ml/L doses there was no survival throughout the period of the experiment p
Keywords: Toxicity; Tadpole; Cassava Effluent; Cyanide; Garri